2022
DOI: 10.47487/apcyccv.v3i1.200
|View full text |Cite
|
Sign up to set email alerts
|

Complicaciones mecánicas posinfarto de miocardio en un hospital de referencia nacional

Abstract: Objetivo. Determinar las características clínicas, terapéuticas y la mortalidad intrahospitalaria de los pacientes con complicaciones mecánicas posinfarto de miocardio (IM). Materiales y métodos. Estudio observacional, descriptivo y retrospectivo. Se incluyó a pacientes > 18 años con diagnóstico de complicación mecánica pos-IM hospitalizados en el Instituto Nacional Cardiovascular (INCOR) en Lima-Perú, del 1 de enero de 2017 hasta el 31 de diciembre de 2021. Se estudiaron variables clínicas, terapéuticas, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…It has been reported that surgery in the first 24 hours has the highest mortality (>60%), within the first seven days the mortality is 54.1%, compared to after seven days when the mortality decreases to 18.4% [ 5 , 6 ]. In our country, a mortality of 50% has been reported in patients with isolated VSR, and CS has been identified as one of the main complications (41.7%) in them [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that surgery in the first 24 hours has the highest mortality (>60%), within the first seven days the mortality is 54.1%, compared to after seven days when the mortality decreases to 18.4% [ 5 , 6 ]. In our country, a mortality of 50% has been reported in patients with isolated VSR, and CS has been identified as one of the main complications (41.7%) in them [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular septal rupture (VSR) is an uncommon mechanical complication of myocardial infarction that occurs between the third and fifth day of evolution and is usually complicated by cardiogenic shock (CS) resulting in high in-hospital mortality [ 1 , 2 ]. The optimal timing of intervention remains controversial [ 1 ], especially in patients with CS and multiorgan failure, where the early use of mechanical circulatory support (MCS) devices such as peripheral venoarterial extracorporeal membrane oxygenation (VA ECMO) in the preoperative period and delayed surgical repair of VSR have been associated with lower mortality [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%